Molecular evidence of potential novel spotted fever group rickettsiae, Anaplasma and Ehrlichia species in Amblyomma ticks parasitizing wild snakes - Kai Ling Kho; Fui Xian Koh; Sun Tee Tay (Parasites & Vectors, 2015)
Abstract Background Amblyomma ticks parasitize a wide range of animals in tropical regions. This study describes the identification of Amblyomma ticks from wild snakes in Malaysia and the detection of potential human pathogens such as Rickettsia, Anaplasma, Ehrlichia and bartonellae in the ticks. Findings Twenty one adult ticks (twelve A. varanense and nine Amblyomma helvolum ticks) identified from seven Python molurus snakes in Sepang and a pool of six A. helvolum ticks from a Naja sumatrana snake in Johore, Malaysia were investigated in this study. Amplification of the citrate synthase (gltA), 190-kDa surface antigen gene (ompA), 135-kDa surface antigen (ompB) and surface cell antigen (sca4) genes followed by sequence analysis confirmed the presence of two potential novel spotted fever group rickettsiae in the ticks. Candidatus Rickettsia sepangensis from an engorged A. varanense tick demonstrated high sequence similarity to Rickettsia tamurae; while Candidatus Rickettsia johorensis from two samples (individual and pooled) of A. helvolum and two A. varanense ticks were closely related to Rickettsia raoultii. Anaplasma and Ehrlichia DNA were detected from seven and two ticks, respectively. No bartonellae was detected from any of the ticks. Conclusion The finding in this study suggests that Amblyomma ticks parasitizing wild snakes may serve as reservoir hosts and carriers for rickettsioses, anaplasmosis and ehrlichiosis in this region.